Upaya Peningkatan Ketrampilan Kader dalam Deteksi Dini kanker Payudara dengan Pemeriksaan Payudara Sendiri (SADARI) di Posyandu Tanggul Asri RW 10 Kelurahan Kadipiro Kecamatan Banjarsari Surakarta - Wulandari, Retno; Wijayanti, Wijayanti; Hapsari, Erlyn; Widyastutik, Desy; Putri H, Syafinatus (Jurnal Salam Sehat Masyarakat (JSSM), 2022)
Data from Riskesdas in 2013 and 2018 showed an increase in cancer prevalence in Indonesia from 1.4% to 1.49%. Screening is a government effort or a simple and easy test carried out on a healthy population with the aim of distinguishing people who are sick or at risk of contracting the disease among healthy people. One form of increasing public awareness about the symptoms and signs of cancer, one of which is the provision of public education about breast self-examination (BSE). Based on the results of interviews with cadres at Posyandu Tanggul Asri RW 10, Kadipiro Village, Banjarsari District, Surakarta, cadres have never received counseling about early detection of breast cancer with BSE. The purpose of this community service is that it is hoped that the skills of cadres in carrying out BSE will increase. The methods used in this community service activity are lectures, demonstrations, discussions / questions and answers. From the results of the implementation of coaching and counseling for 1 day which was attended by 12 cadres, it turned out that the activity received a good response by the cadres. Cadres become more aware of early detection of breast cancer and can demonstrate how to do BSE. The conclusion of this Community Service Activity is that Cadres understand early detection of breast cancer with BSE.